Overview of the characteristics, knowledge and actions of pregnant women with anemia on the benefits of beet juice consumption at Romauli Clinik Marelan Year 2025 - R. Oktaviance S; Janiartika Sihura; Merlina Sinabariba; Risda Manik (Science Midwifery, 2025)
Beetroot (beta vulgaris) contains flavonoids that are very useful in the formation of red blood cells (erythrocytes). The nutritional content of the beet plant is folic acid, potassium, fiber, vitamin C, magnesium, tryptophan, iron, copper, and phosphorus. Effective non-medical treatment to optimize hemoglobin levels in pregnant women by drinking beet juice. Among all types of fruits, Beetroot is recognized as a fruit that has a lot of folic acid-rich content reaching 43 mg. Purpose of the study: To find out the description of the characteristics, knowledge and actions of pregnant women with anemia on the benefits of beet juice consumption. Research method: this study is descriptive. The collection technique is carried out by purposive sampling with 30 respondents. Pregnant women with elementary education are 2 people (6.7%), junior high school (3.3%), high school (66.7%) and 7 people in college (23.3%). Based on the age of 20-35 years as many as 28 people (93.3%) and the age of >35 years as many as 2 people (6.7%). Based on the characteristics of dominant income, 27 people (90%) do not earn and 3 people have sufficient income (10%). Based on the dominant occupation, 27 (90%) of non-working mothers and 3 working mothers (10%) of them worked. Based on the Gravida, the Primigravida respondents are 14 people (46.7%) and the Multigravida are 16 people (53.3%). Conclusion: Based on the results of the study, it is shown that the majority of high school education, the majority of mothers are 20-35 years old, the majority of mothers' income is not income, the majority of mothers' jobs are not working, the majority of Gravida mothers are Multigravida. The majority of mothers' knowledge is sufficient to know the benefits of consuming beet juice, and the majority of pregnant women do not consume beet juice. It is expected that health workers will increase educational services to pregnant women on the benefits of beet juice so that anemia in pregnant women can be reduced.